Tourism persistence in the Southeastern European countries: The impact of covid-19 - Guglielmo Maria Caporale; Luis A. Gil-Ala\~na; Amir Imeri (Cogent Economics & Finance, 2023)
This paper examines tourism persistence in a group of Southeastern European (SEE) countries (Albania, Bosnia, Bulgaria, Croatia, Montenegro, North Macedonia, Serbia and Slovenia) by applying fractional integration methods to monthly data on foreign tourist arrivals and overnight stays. The results indicate that the COVID-19 pandemic has increased the degree of persistence of these series as measured by the fractional differencing parameter; specifically, it has removed the mean reversion property in some countries. In addition, it has reduced the importance of the seasonal component.
Keywords: C13; C22; L83; N74; Z32; 330; COVID-19; fractional integration; persistence; SEE; shocks; tourism